On Using Lagrangian Drift Simulations to Aid Interpretation of in situ Monitoring Data - Callies, Ulrich; Kreus, Markus; Petersen, Wilhelm; Voynova, Yoana G. (Frontiers in Marine Science, 2021)
One key challenge of marine monitoring programs is to reasonably combine information from different in situ observations spread in space and time. In that context, we suggest the use of Lagrangian transport simulations extending both forward and backward in time to identify the movements of water bodies from the time they were observed to the time of their synopsis. We present examples of how synoptic maps of salinity generated by this method support the identification and tracing of river plumes in coastal regions. We also demonstrate how we can use synoptic maps to delineate different water masses in coastal margins. These examples involve quasi-continuous observations of salinity taken along ferry routes. A third application is the synchronization of measurements between fixed stations and nearby moving platforms. Both observational platforms often see the same water body, but at different times. We demonstrate how the measurements from a fixed platform can be synchronized to measurements from a moving platform by taking into account simulation-based time shifts.